Building blocks for powerful ideas: designing a programming language to teach the beauty and joy of computing - Mönig, Jens (2020)
Snap! is a cloud-native graphical programming environment and an online community. It is the programming language made for UC Berkeley’s popular introductory CS course named “The Beauty and Joy of Computing”. Snap! is taught in colleges and high schools across the U.S. from Palo Alto to Philadelphia. It has been translated to more than 40 languages and is used around the world—from Göttingen to Beijing—for teaching and research. Snap! has been designed for inclusion. Its low floor welcomes beginners and its multi-media capabilities invite creative thinkers of all ages. At the same time, Snap! offers sophisticated abstractions that make it suitable for an intellectually rigorous introduction to computer science.